Abnormalities in liver function and coagulation profile following the Fontan procedure. Issue 1 (1st July 1999) - van Nieuwenhuizen, R C; Peters, M; Lubbers, L J; Trip, M D; Tijssen, J G P; Mulder, B J M
Abstract : OBJECTIVE: To investigate liver function and coagulation disorders in patients with a Fontan circulation at different time intervals after surgery. DESIGN: Retrospective analysis of clinical data and cross sectional study relating liver function and coagulation profile to time since surgery, in 28 surviving patients after the modified Fontan procedure. PATIENTS: 20 patients (71%) with atriopulmonary anastomosis, seven (25%) with atrioventricular anastomosis, and one (4%) with total cavopulmonary connection. Follow up ranged from 2.0 to 21.8 years (mean 11.1). RESULTS: Abnormal liver function tests, mainly reflecting cholestasis, were present in 21 patients who had a significantly longer follow up (p < 0.01). Protein synthesis was normal in almost all patients. Coagulation profile showed abnormalities in 22 patients. "Procoagulant" abnormalities—that is, decreased plasminogen and protein C activity—were found in 11 and five patients, respectively. The extent of these abnormalities was less in patients with a longer follow up. Anticoagulant abnormalities were factor V deficiency in 16 patients and factor VII deficiency in 17, resulting in a prolonged prothrombin time in 19 patients. Thirteen patients had both pro- and anticoagulant abnormalities. A prethrombotic state was present in five patients, with a significantly longer mean time interval since surgery (p = 0.05). Thus, although the individual procoagulant indices decreased with increasing time intervals since surgery, a prethrombotic state was found particularly in patients with a long term follow up. CONCLUSIONS: Mild cholestasis was mainly present in Fontan patients with a long duration of follow up. Along with laboratory procoagulant abnormalities indicating a prethrombotic state, anticoagulant abnormalities were also present. The coagulation profile varied at different time intervals after surgery. Thus detailed evaluation should be performed regularly, and the use of anticoagulants should be considered in every patient. Long term prospective studies are needed to evaluate the individual fluctuations of coagulation profile over time following a Fontan procedure.